Online distance learning amidst COVID-19 pandemic among university students: a practicality of partial least squares structural equation modelling approach / Muhammad Faizal Samat ... [et al.] - Samat, Muhammad Faizal; Awang, Nur Amalina; Hussin, Siti Nor Adawiah; Mat Nawi, Farahiyah Akmal Mat Nawi (Universiti Teknologi MARA, 2020)
World Health Organization declared the coronavirus disease 2019 (Covid-19) outbreak, caused by severe acute respiratory syndrome coronavirus 2 to be a pandemic on March 12, 2020. In response to that, Malaysia has announced movement control order effective on March 18, 2020, leading to the neartotal closures of education centers. University closures impact not only students, lecturers, and families, but have far-reaching economic and societal consequences. In response to that, Universiti Teknologi MARA (UiTM) has introduced the use of online distance learning and open educational applications and platforms that lecturers can use to reach learners remotely and limit the disruption of education. Even though UiTM has already adopted the integrated face-to-face and online learning approach in the classroom since many years ago, however, the commencement of solely using online learning platforms, in the absence of faceto-face meetings is challenging. In addition, it is also crucial to note that the previous study on the determinants of the intention and effective use of online distance learning is scarce. Thus, this study seeks to identify the significant relationship between the intention and the effective use of an ODL among the students. Findings from this study reveals that four out of five determinants (performance expectancy, effort expectancy, social influence, facilitating condition and intrinsic value) found to be significantly related with the behavioral intention of the students to use online distance learning. Behavioral intention also was found to be significant with use behavior. Although the intrinsic values (new determinants) have contributed to the theory, it is recommended that the same study will be carried out to the entire education center, either public or private.